Modelling and analysis of a NTVV-SVM based three-level twin-step matrix converter - Ansari, Shamsher; Chandel, Aseem; ., SMIEEE; Ali Sheikh, Zulfiqar (International Journal of Engineering and Technology, 2018)
Recently the tremendous advancement has been seen in the field of matrix converter topology. For high power drive applications, industries often need high power AC-AC converters like three level matrix converter because it is having the ability to generate a set of balanced sine waves for inputs as well as outputs. The three level matrix converters possess better output performance with reduced harmonic contents compared to all two-stage indirect matrix converters. In this matrix converter topology, the idea of neutral-point clamped-VSI is employed to the inversion step of the matrix converter circuitry. To control the power switches the gate signals are produced using NTVV based space vector modulation. To justify the theoretical study a complete model of a three-level twin-step matrix converter has been designed in Matlab/Simulink and its performances are analysed.Â Â